MULTI-PORT ELECTRIC STIMULATION SYSTEM USING HIGH SPEED PROCESSORS - Lopez de la Fuente; Martha Salome (European Scientific Journal, ESJ, 2014)
Electric signals are used in research areas as stimulus in tests: in body fluid samples to find a specific type of cells, particles, viruses or bacteria, in water samples to find pollutant agents, in blood samples to count T-Lymphocytes as cancer evidence, in food samples to determine safety, in prosthetics development for functional tests, in biotechnology to determine cell development stage, and several other fields. Currently, generic equipment such as standard signal generators is used to deliver the needed electric signals to the experimental setting. Generic equipment requires knowledge in the electric field, that researchers in biological and medicine fields do not have. Besides, it is expensive and delivers a limited type of signal waveforms. This paper presents the idea, design, implementation, and results of a flexible, programmable, multi-purpose device for delivering multi-waveform signals for a variety of applications. The idea is to develop a device which delivers different waveforms, single or superimposed, to several ports, where signal parameters such as amplitude, frequency, phase, waveform and repetition pattern are defined by the user. The design is based on a high speed processor, a Harvard architecture memory, a communication/configuration port, and 8-bit IO ports. A prototype is developed using an ARM processor based board, a C++ application program, and a User Interface. Specifications achieved: self contained, configurable, programmable, Vout up to 200Vpp, frequency 1Hz- 40kHz, 4 waveforms (sinusoid, triangle, square, and saw-tooth), single, dual, or superimposed signals, waveform combination, single triggered outputs, continuous execution, and programmable repetition patterns.